Analisis Komunikasi Interpersonal Orang Tua dan Remaja Tunarungu Korban Bullying dalam Film Dear Frankie - Yustina Yustina; Maulina Larasati P; Vera Wijayanti S (Jurnal Syntax Admiration, 2025)
Cases of bullying or what is known as bullying are a problem that never ends in society, especially among children and teenagers. This bullying behavior is carried out by stronger individuals against weaker individuals with the aim of hurting and intimidating. So children with special needs who have physical and mental limitations are often the victims of bullying. Problems that often occur in society require strong support from within or from the family to face external problems or the victim's environment. Therefore, interpersonal communication between parents is very important for children with special needs who are victims of bullying. This is presented in the film Dear Frankie, where there is interpersonal communication between Frankie's parents and Frankie, the child who is deaf. Where Frankie can act mature, independent and confident in facing his friend who is a bully.